Impact of ischemic preconditioning combined with aerobic exercise on 24-h ambulatory blood pressure in men with prehypertension and stage 1 hypertension - Jang, Min-Hyeok; Kim, Dae-Hwan; Han, Jean-Hee; Kim, Seok-Ho; Kim, Jung-Hyun (Frontiers in Physiology, 2024)
IntroductionA single bout of aerobic exercise is known to induce a temporary reduction in post-exercise blood pressure termed post-exercise hypotension (PEH). Meanwhile, an ischemic preconditioning (IPC), a series of short ischemia-reperfusion intervention, has also shown antihypertensive effects showing a potential nonpharmacologic intervention for hypertension. While the acute BP reduction effects of aerobic exercise and IPC are individually well-investigated, it remains unclear if combining both interventions has an additive effect on PEH.MethodsA total of twelve pre- or hypertensive men (six prehypertension, six stage 1 hypertension) underwent either 30 min of aerobic exercise at 50% VO2peak (CON) or IPC before exercise, in a counterbalanced order. IPC involved inflating cuffs on both thighs to 200 mmHg for 5 min, alternating between right and left thighs for three cycles, totaling 30 min. Brachial BP was measured during exercise and 1-h post-exercise recovery whereas muscle oxygen saturation (SmO2) from the rectus femoris was monitored using NIRs during exercise and recovery. Heart rate variability (HRV) and baroreflex sensitivity (BRS) together with a head-up tilt test (at 0 and 50°) were measured at the pre-test, post-test, and 24-h post-test. After the completion of each experiment, 24-h ambulatory blood pressure (ABP) was monitored to assess post-exercise hypotension within a 24-h window.ResultsBP and heart rate responses during exercise and 1-h recovery did not differ between conditions while SmO2 was significantly elevated during exercise in IPC (p = 0.004). There was no difference in HRV and supine BRS. However, significantly reduced titled BRS after exercise was found in CON while IPC preserved BRS similar to pre-exercise value, extending to 24-h post period (p = 0.047). ABP monitoring revealed a significant reduction in systolic BP during sleep in IPC compared to CON (p = 0.046).ConclusionThe present findings suggest that IPC with a single session of aerobic exercise results in a notable decrease in systolic ABP, particularly during sleep, compared to aerobic exercise alone. This supplementary antihypertensive effect was associated with a sustained BRS, persisting up to 24 h in contrast to the significant decrease observed in CON. Future studies are warranted to investigate long-term adaptations to IPC.